2016
DOI: 10.1002/1873-3468.12491
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic iron–sulfur cluster transfer—a proposed kinetic pathway for reconstitution of glutaredoxin 3

Abstract: Iron-sulfur clusters are ubiquitously conserved and play essential cellular roles. The mechanism of Fe-S cluster biogenesis involves multiple proteins in a complex pathway. Cluster biosynthesis primarily occurs in the mitochondria, but key Fe-S proteins also exist in the cytosol. One such protein, glutaredoxin 3 (Grx3), is involved in iron regulation, sensing and mediating [2Fe-2S] cluster delivery to cytosolic protein targets, but the cluster donor for cytosolic Grx3 has not been elucidated. Herein, we deline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 63 publications
5
32
0
Order By: Relevance
“…Which is the system donating [2Fe–2S] 2+ clusters to the apo complex is still under investigation. A possible pathway, that has been recently proposed, involves the mitochondrial ISC assembly machinery: the de novo biosynthesis of the [2Fe–2S] 2+ cluster on mitochondrial ISCU2 is followed by cluster export, as [2Fe–2S](GS) 4 complex, via a membrane transporter; then, the [2Fe–2S] cluster is believed to be uptaken by the cytosolic form of ISCU2, which delivers it to cytosolic form of NFU1, which finally transfers the cluster to GLRX3 [189192]. This molecular process is, however, only based on in vitro information, and experimental evidences from in vivo data are required to definitively validate it.…”
Section: The Contribution Of Solution Nmr To Understand Molecular Aspmentioning
confidence: 99%
“…Which is the system donating [2Fe–2S] 2+ clusters to the apo complex is still under investigation. A possible pathway, that has been recently proposed, involves the mitochondrial ISC assembly machinery: the de novo biosynthesis of the [2Fe–2S] 2+ cluster on mitochondrial ISCU2 is followed by cluster export, as [2Fe–2S](GS) 4 complex, via a membrane transporter; then, the [2Fe–2S] cluster is believed to be uptaken by the cytosolic form of ISCU2, which delivers it to cytosolic form of NFU1, which finally transfers the cluster to GLRX3 [189192]. This molecular process is, however, only based on in vitro information, and experimental evidences from in vivo data are required to definitively validate it.…”
Section: The Contribution Of Solution Nmr To Understand Molecular Aspmentioning
confidence: 99%
“…Also, in contrast to native protein, the G208C variant is unable to take up the [2Fe-2S](GS) 4 complex [1]. Likewise, the mutant protein is unable to receive a [2Fe-2S] cluster from typical iron-sulfur scaffold proteins such as Isa1 and IscU (Table 5), which have been shown to deliver a cluster into native NFU1 [10, 14]. Current models for Fe/S cluster biogenesis indicate that transfer from IscU is promoted with assistance from heat shock chaperone proteins [16, 37, 47, 55].…”
Section: Discussionmentioning
confidence: 99%
“…The point mutation results in a changed preference for the glutaredoxins. Our previous work has indicated that [2Fe-2S] cluster from native NFU1 to apo Grx3 was a kinetic sink at 36000 M −1 min −1 , while transfer to Grx2 occurred, but at around the same level as other transfers from NFU1 (Table 5) [10, 14]. However, the mutant form of the protein now kinetically prefers cluster transfer to Grx2 by increasing the second-order rate constant seven-fold over transfer to Grx3, which decreased by three-fold.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations